Activities of daily living (ADL) and instrumental activities of daily living (IADL) disability in Swedish 85-year-olds born three decades apart—findings from the H70 study. (9th June 2021) - Falk Erhag, Hanna; Wetterberg, Hanna; Johansson, Lena; Rydén, Lina; Skoog, Ingmar
Abstract: Objective: Older adults make up the fastest growing segment of the population, and disability rates increase with age. There is much debate whether later born cohorts of 85-year-olds will face the same disability rates as earlier born cohorts. This study aimed to examine ADL and IADL disability in three birth cohorts of Swedish 85-year-olds born three decades apart, examined in 1986–87, 2008–10 and 2015-16, as well as potential factors associated with ADL and IADL disability in these birth-cohorts. Methods: Systematically selected population-based birth cohorts of 85-year-olds (n = 1, 551) from the Gothenburg H70 Birth Cohort studies, Sweden, born in 1901–02 (n = 494), 1923–24 (n = 571) and 1930 (n = 486) and examined with identical methods. Disability was defined as a need for assistance in any ADL/IADL activities. Results: ADL/IADL disability decreased between cohorts in both men and women (from 76.7% in 1986–87, to 58.4% in 2008–10, and 48.4% in 2015–16, P -value trend <.001). Factors associated with ADL/IADL disability varied between cohorts, although dementia and depression increased the odds of disability in all three birth cohorts. Conclusion: Later born cohorts of 85-year-olds face less ADL/IADL disability compared to earlier born cohorts. As disability poses a significant financial burden on healthcare services, our findings might contribute to a more positive view on global ageing and the demographic challenges ahead. However, it might also be that in later born cohorts, ADL/IADL disability affects people at later ages, but due to increased longevity, the total number of years in late-life with a functional disability will remain the same.